Targeted Sensory System Neuromodulation Improves Sensorimotor and Cognitive Deficits After Brain Injury: Bridging Mechanisms to Practice - Qin Zhang; Zhen Pang; Rongrong Lu; Hua He; Ulf Ziemann; Zhengrun Gao (Neural Plasticity, 2025)
Brain injury, including stroke and traumatic brain injury (TBI), is a leading cause of death and disability worldwide, and limited spontaneous neuroplasticity often results in persistent neurological impairments. Neuromodulation has the potential to enhance brain reorganization, but when targeting motor pathways, it might yield unsatisfactory rehabilitation of sensorimotor and cognitive defecits. Given the essential role of sensory system in both motor and nonmotor functioning, there is growing interest in targeting the sensory system for sensorimotor and cognitive recovery after brain injury. Emerging research is showing that neuromodulation of different components of the sensory pathway can induce brain remodeling at the synaptic, cellular, and circuit levels. Preclinical and clinical trails have demonstrated that sensory modulation strategies can restore sensorimotor and cognitive functions after brain injury. These evidence raised the potential of targeted sensory system neuromodulation to facilitate comprehensive rehabilitation after brain injury through augmenting brain remodeling. Challenges, such as the lack of large-scale clinical trials and limited understanding of the neural basis of neuromodulation effects still need to be addressed. Future advancements in multimodal and closed loop stimulation approaches, as well as sensory feedback brain-computer interfaces, hold promise for providing more effective and personalized treatments for patients with brain injury.